ANALYSIS OF THE ELECTROPHYSICAL AND PHOTOELECTRIC PROPERTIES OF NANOCOMPOSITE POLYMERS BY THE MODIFIED KELVIN PROBE - K. U. Pantsialeyeu; A. U. Krautsevich; I. A. Rovba; V. I. Lysenko; R. I. Vorobey; O. K. Gusev; A. L. Zharin (Приборы и методы измерений, 2017)
At present for analysis of the homogeneity of materials properties are becoming widely used various modifications of a scanning Kelvin probe. These methods allow mapping the spatial distribution of the electrostatic potential. Analysis of the electropotential profile is not sufficient to describe any specific physical parameters of the polymer nanocomposites. Therefore, we use an external energy impact, such as light. Purpose of paper is the modification of the Kelvin scanning probe and the conduct of experimental studies of the spatial distribution and response of the electrostatic potential of the actual polymer nanocomposites to the optical probing.Carried out the investigations on experimental Low density polyethylene composites. Carbon nanomaterials and nanoparticles of silicon dioxide or aluminum as fillers are used. As a result, maps of the spatial distribution of the electrostatic potential relative values and the surface photovoltage. Statistical analysis of the electrophysical and photoelectric properties homogeneity, depending on the component composition of the composites carried out. In addition, with reference to matrix polymers, the Kelvin scanning probe, in combination with the optical probing, made it possible to detect a piezoelectric effect. The latter, can used as a basis for the development of new methods for studying the mechanical properties of matrix polymers.